Pollutants: a candidate as a new risk factor for osteoarthritis—results from a systematic literature review. Issue 2 (14th June 2022) - Deprouw, Camille; Courties, Alice; Fini, Jean-Baptiste; Clerget-Froidevaux, Marie-Stéphanie; Demeneix, Barbara; Berenbaum, Francis; Sellam, Jérémie; Louati, Karine
Abstract : Background: Considering non-classical environmental risk factors for osteoarthritis (OA), a systematic literature review (SLR) was performed to summarise existing knowledge on associations between OA and pollutants. Methods: PubMed was used to identify studies reporting data on OA and pollutants in humans (examples of MeSH terms: "Pesticides" or "Polychlorinated Biphenyls" or 'Lead'). Reports included epidemiological clinical studies, pollutant assessments in ex vivo OA joint, and in vitro effects of pollutants on chondrocytes. Results: Among the 193 potentially relevant articles, 14 were selected and combined with 9 articles obtained by manual search. Among these 23 articles there were: (1) 11 epidemiological studies on the relationship between OA and pollutants exposure, (2) 8 on pollutant concentrations in ex vivo OA joint, (3) 4 on the in vitro effects of pollutants on human chondrocytes. Epidemiological studies investigating mainly chlorinated and fluorinated pollutants suggested a possible link with OA. In cross-sectional studies, radiographic knee OA prevalence increased with higher serum lead levels. There was also a relationship between serum lead levels and serum/urine joint biomarkers. A high concentration of heavy metals in the cartilage tidemark was found in ex vivo joints. In vitro, the viability of chondrocytes was reduced in presence of some pollutants. However, the level of knowledge currently remains low, justifying the need for new methodologically sound studies. Conclusions: This SLR supports the hypothesis of a possible involvement of pollutants in OA disease risk. Large-scale epidemiological and biological studies and ideally big-data analysis are needed to confirm that pollutants could be risk factors for OA.